2019
DOI: 10.3390/land8010008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Future Land Use Change on Large Carnivores Connectivity in the Polish Carpathians

Abstract: The Polish Carpathians, like many mountain areas in Europe, are currently facing dynamic land use changes that will shape their future landscapes. As there are many different possible scenarios of potential change, we compared three different land use scenarios up until the year 2060 and assessed their impact on the potential habitat connectivity of two large carnivores—wolf (Canis lupus) and lynx (Lynx lynx). We first analysed the main directions of change within and outside the pan-European wildlife corridor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
(81 reference statements)
0
4
0
1
Order By: Relevance
“…Human settlements are expanding, and new infrastructures are built deeper into species habitat as land procurement becomes more and more difficult. According to census data from the government of Pakistan, an increase of 36% was reported in the population of AJK (density: 302 people/km 2 ) from 1998 (2,972,523) to 2017 (4,045,366). Similarly, the human population in KP ((density: 300 people/km 2 )) increased by 72% from 17,743,645 in 1998 to 30,523,371 in 2017 (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human settlements are expanding, and new infrastructures are built deeper into species habitat as land procurement becomes more and more difficult. According to census data from the government of Pakistan, an increase of 36% was reported in the population of AJK (density: 302 people/km 2 ) from 1998 (2,972,523) to 2017 (4,045,366). Similarly, the human population in KP ((density: 300 people/km 2 )) increased by 72% from 17,743,645 in 1998 to 30,523,371 in 2017 (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have concluded that LULCC activities are intensifying, and that wildlife habitat is increasingly being developed for agriculture and infrastructure [2,3]. Settlement development and the associated expansion of transportation networks are among the most influential LULCC affecting current species spatial distributions and habitat continuity [4,5]. Studies have also shown further expansion of already built-up areas into natural habitats [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Although settlements are generally characterised by relatively small footprints, they nonetheless have a huge impact (Meyfroidt et al, 2022) and influence on both neighbouring areas and more distant land systems. Local settlement triggers the loss of natural areas (van Vliet, 2019); increases road network development, landscape fragmentation (Ibisch et al, 2016), light (Hölker et al, 2010) and noise pollution (Merrall & Evans, 2020); and adversely impacts connectivity among habitats (Kaim et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tutupan lahan menjadi salah satu indikator utama kerusakan kawasan. Kehilangan habitat akibat perubahan tutupan lahan menjadi ancaman utama terhadap keberadaan satwa liar (Sintayehu & Kassaw, 2019;Kaim, et al, 2019;Martinuzi et al, 2015). Disebutkan bahwa dengan habitat kurang tersedia,populasi satwa liar di seluruh dunia telah menurundan 20-35% dari mamalia terancam punah (Schipper et al, 2008 Tingkat Kerusakan Kawasan = (40*tutupan lahan) + (20*frekuensi kebakaran) + (20*sensivitas ekologi) + (10*areal berkanal) + (10*sensivitas sosial)…”
Section: Parameter Frekuensi Kebakaranunclassified